Interventioner med informations- och kommunikationsteknologiska hjälpmedel samt effekten av interventionerna för barn, ungdomar och unga vuxna 7-20 år : En litteraturöversikt - Björkman, Sara (2013)
The purpose of this literature review is to describe interventions with information and communication technology aids and the effect of interventions for children, adolescents and young adults 7-20 years. Data collection was conducted through a systematic search of the databases AMED, Chinal, PubMed and PSYKinfo via Luleå University Library of predefined keywords. Even a manual search through the reference lists was conducted. Ten quantitative articles were included in the study and were assessed probative value and quality review. None of the articles were made in Sweden. Articles were then analyzed on the basis of similarities and differences. The analysis revealed three sub-categories: Interventions to facilitate everyday activities, interventions in school and studies evidence and interventions' effect. ICT tools are used either directly in the activity or in preparation for an activity in everyday life or in school. The age of the majority of the participants were 15-20 years old, most common diagnoses were various developmental disorders, neuropsychiatric disorders, dyslexia and learning difficulties. Four of the articles describe occupational therapy interventions with ICT tools. The findings of the literature review cannot be generalized, results provide an indication of a need for further research in the area to allow activities in daily life and in school. Validerat; 20130627 (global_studentproject_submitter)